Canonical Wnt/β‐catenin and Notch signaling regulate animal/vegetal axial patterning in the cephalochordate amphioxus. Issue 1 (4th October 2018) - Onai, Takayuki
Abstract : In bilaterians, animal/vegetal axial (A/V) patterning is a fundamental early developmental event for establishment of animal/vegetal polarity and following specification of the germ layers (ectoderm, mesoderm, endoderm), of which the evolutionary origin is enigmatic. Understanding A/V axial patterning in a basal animal from each phylum would help to reconstruct the ancestral state of germ layer specification in bilaterians and thus, the evolution of mesoderm, the third intermediate cell layer. Herein, data show that the canonical Wnt/β‐catenin (cWnt) and Notch signaling pathways control mesoderm specification from the early endomesoderm in the basal chordate amphioxus. Amphioxus belongs to the deuterostome, one of the main superphyla in Bilateria. In the present study, genes ( tcf, dsh, axin, gsk3β ) encoding cWnt components were expressed in the endomesoderm during the gastrula stages. Excess cWnt signaling by BIO, a GSK3 inhibitor, expanded the expression domains of outer endomesodermal genes that include future mesodermal ones and suppressed inner endomesodermal and ectodermal genes. Interfering Notch signaling by DAPT, a γ‐secretase inhibitor, resulted in decreased expression of ectodermal and endomesodermal markers. These results suggest that cWnt and Notch have important roles in mesoderm specification in amphioxus embryos. The evolution of the mesoderm is also discussed.